Blood group distribution and its association with bleeding time and clotting time among medical students - Adhikari, Bijaya; Maharjan, Niroj (Asian Journal of Medical Sciences, 2024)
Background: Blood group, bleeding time (BT), and clotting time (CT) are routinely performed tests in the hospital, especially before any surgeries and blood transfusion. Aims and Objectives: The objective of the study is to see if there is any association of blood group with BT and CT and the gender difference in BT and CT. Materials and Methods: A cross-sectional study was conducted among 132 medical students of 1st year in the hematology laboratory of the Department of Physiology in KIST Medical College from June 2022 to September 2022. The blood group was determined by a simple agglutination method. BT was determined by Dukes method whereas CT was determined using capillary tube method. Data were analyzed using SPSS-20 software. The difference in BT and CT among various blood groups was done using the ANOVA test and P≤0.05 was considered significant. Student’s t-test was used to find the association of gender with BT and CT. Results: Both BT and CT were found to be more in males than females. However, the difference was significant only in the mean BT (P=0.05, Table 2). There was no significant difference in the mean BT among various blood groups but CT was found to be significant (P=0.05). Conclusion: Our study showed the tendency of bleeding to be more in blood Group B individuals. Multicentric study including a larger population with plasma level of von Willebrand factor might be helpful to verify findings and identify the risk group.